Farmers' export market participation decisions in transition economies: a comparative study between Armenia and Uzbekistan. Issue 1 (1st January 2016) - Bobojonov, Ihtiyor; Teuber, Ramona; Hasanov, Shavkat; Urutyan, Vardan; Glauben, Thomas
ABSTRACT: The Russian import ban on Western food products has stimulated a discussion about whether and how countries in Central Asia and Caucasus might benefit from this political decision by expanding their agrifood exports to Russia. Given this background, our study compares farmers' willingness to participate in export markets in Armenia and Uzbekistan. Discussions are based on the analysis of surveys of 400 farmers from each country conducted in the spring of 2015. The results show that farmers already participating in local markets have a higher motivation to engage in the production of exportable commodities when a sudden export opportunity emerges. Beyond this general finding, the relative importance of farm and infrastructure characteristics were identified under different commercialization levels. Although both types of factors have been identified as important determinants in the existing literature, our analysis provides further evidence. We demonstrate that variables related to farm characteristics play a rather crucial role in more subsistence-oriented small-scale farming systems as found in the case of Armenia. In contrast, infrastructure may become more important than farm endowments in more commercially oriented farming systems such as observed in Uzbekistan.